Heat pump efficiency in fifth generation ultra-low temperature district heating networks using a wastewater heat source. (1st December 2021) - Reiners, Tobias; Gross, Michel; Altieri, Lisa; Wagner, Hermann-Josef; Bertsch, Valentin
Abstract: Ultra-low district heating (ULTDH) networks are operated at temperatures below 30 °C. However, the temperatures supplied are still too low for direct heating of the consumers. Heat pumps use the heating network as a source and can supply the consumers with space heating and domestic hot water as needed. Although individual manufacturers provide performance figures for the source temperature of 20 °C, these are usually derived from extrapolation from standard conditions with source temperatures of 0 °C and 10 °C. Up to now practical measurements are missing how efficiently heat pumps work in an ULTDH network environment and how the network temperature spread affects the performance. In this paper test rigs are used to investigate heat pumps under the conditions in ULTDH networks at a network supply temperature of 20 °C. It is shown that heat pumps can operate up to twice as efficient as with a geothermal probe. Furthermore, the network temperature spread has a significant influence on the performance of the heat pump. Heat pumps operate significantly better with a low source temperature spread. Highlights: Test rig measurements for heat pump efficiency in an ULTDH network environment. Network supply temperature of 20 °C. Impact of the network temperature spread on the heat pump performance. COP maximum COP of 10 at a source outlet temperature of 17 °C in the ULTDH network. Heat pumps compressor limitations must be considered in ULTDH networks.